Children and the changing family : between transformation and negotiation - Jensen, An-Magritt.; McKee, Lorna (London ; New York : RoutledgeFalmer, 2003)
This timely and thought-provoking book explores how social and family change are colouring the experience of childhood.
Childhood and family time: a changing historical relationshipAfterword: Changing childhoods: a case study; Notes; Index.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Children -- Social conditions; Children -- Family relationships; Work and family; Children of divorced parents; Social change; Social Change; Enfants -- Conditions sociales; Enfants -- Relations familiales; Travail et familles; Enfants de divorcés.; Changement social; Enfance -- Relations familiales; SOCIAL SCIENCE -- Children's Studies; Children -- Family relationships; Children of divorced parents; Children -- Social conditions; Social change; Work and family; Kinderen; Gezinsrelaties; Sociale verandering; Chômage.; Changement social; Enfant; Enfant du divorce; Famille; Relation familiale; Travail; Electronic books